Seeing red - Lufuku, Joseph Mawa (Technical Centre for Agricultural and Rural Cooperation, 1998)
Joseph Mawa Lufuku, of the Centre de promotion sociale et agro-alimentaire (CEPROSA) in Kinshasa, Democratic Republic of Congo, writes about the article in the French edition of Spore 65: 'The recommendation 'Don't whiten palm oil' is sound advice...